Industrial training report: SWOT analysis of Raja Permaisuri Bainun Hospital Ipoh, Perak / Ani Nazihah Ahmad Najlan - Ahmad Najlan, Ani Nazihah (Universiti Teknologi MARA, Perlis, 2021)
This is an internship report regarding the Raja Permaisuri Bainun Hospital SWOT analysis where there is an in-depth research on how the SWOT technique applies in this company. It starts with an introduction about Raja Permaisuri Bainun Hospital followed by the history of the hospital itself. It gives a briefing about all the Raja Permaisuri Bainun Ipoh Hospital. This study is a brief discussion of the functions carried out at Raja Permaisuri Bainun Hospital. This hospital, which was constructed in 1891, is one of the largest hospitals in Perak. The hospital is making every effort to face the future challenges by strategically preparing and making the best use of its financial and control. For the smooth running of the finance department, a skilled team of employees has been recruited to represent and deliver quality and productive results. Apart from that, in this report reader will be able to understand more on how the SWOT analysis works in this hospital since Raja Permaisuri Bainun Hospital is responsible for distribution of money to three other hospitals which are Sungai Siput Hospital, Kampar Hospital and Batu Gajah Hospital. In addition, this report will explain and give the reader further details for every strength, weaknesses, opportunities and threats the hospital has discovered for the whole system of this hospital. Furthermore, by using SWOT technique they will be able to see which part that they are best at and which part that they need to change for better management in the future. At the end, I have briefly evaluated the organization according to my learning and concluded my views about its operation. The last part of the report gives suggestions and recommendations for the company’s future